Analysis of the gut and gill microbiome of resistant and susceptible lines of rainbow trout (Oncorhynchus mykiss). Issue 86 (March 2019) - Brown, Ryan M.; Wiens, Gregory D.; Salinas, Irene
Abstract: Commensal microorganisms present at mucosal surfaces play a vital role in protecting the host organism from bacterial infection. There are multiple factors that contribute to selecting for the microbiome, including host genetics. Flavobacterium psychrophilum, the causative agent of Bacterial Cold Water Disease in salmonids, accounts for acute losses in wild and farmed rainbow trout (Oncorhynchus mykiss). The U.S. National Center for Cool and Cold Water Aquaculture has used family-based selective breeding to generate a line of rainbow trout with enhanced resistance to F. psychrophilum. The goal of this study is to determine whether selective breeding impacts the gut and gill microbiome of the F. psychrophilum -resistant as compared to a background matched susceptible trout line. Mid-gut and gill samples were collected from juvenile fish maintained at high or low stocking densities and microbial diversity assessed by 16S rDNA amplicon sequencing. Results indicate that alpha diversity was significantly higher in the mid-gut of the susceptible line compared to the resistant line, while no significant differences in alpha diversity were observed in the gills. Mycoplasma sp. was the dominant taxon in the mid-gut of both groups, although it was present at a decreased abundance in the susceptible line. We also observed an increased abundance of the potential opportunistic pathogen Brevinema andersonii in the susceptible line. Within the gills, both lines exhibited similar microbial profiles, with Candidatus Branchiomonas being the dominant taxon. Together, these results suggest that selectively bred F. psychrophilum -resistant trout may harness a more resilient gut microbiome, attributing to the disease resistant phenotype. Importantly, interactions between host genetics and environmental factors such as stocking density have a significant impact in shaping trout microbial communities. Highlights: Selective breeding results in enhanced resistance (ARS-Fp-R) or susceptibility (ARS-Fp-S) to F. psychrophilum infection. The gut microbiome of the ARS-Fp-R line is less diverse than that of the ARS-Fp-S. line. Mycoplasma sp. constituted a majority of the gut microbiome in both lines, although it was more abundant in ARS-Fp-R. An increased abundance of potential opportunistic pathogens was observed in the ARS-Fp-S line. Stocking density had an impact on the trout microbial communities.